Spirituality Vis-Ã€-Vis Media Adaptability: The Community Of Cirendeu Village West Java - Firdaus, Dany Randa (Proceeding International Conference on Islam and Civilization (ICONIC), 2021)
Several religions are recognized in Indonesia: Islam, Christianity, Catholicism, Hinduism, Buddhism, and Confucianism. However, some beliefs are still being debated, namely the Sunda Wiwitan beliefs, especially those located in the traditional village of Cireundeu, Leuwigajah, South Cimahi sub-district, Cimahi City, West Java. The exciting thing for the writer to examine is the response of Cirendeu Village with its various local wisdom and religious activities to contemporary modern media. This study aims to determine the response of the residents of the traditional village of Cireundeu on the issue and their sociological perspective. Researchers used qualitative methods in conducting this research, so the results obtained were more comprehensive, intact, and holistic. Through interviews with traditional leaders (Pupuhu) in-depth, the authors were able to compile this journal integrally. This study indicates a correlation between religious activities and the openness and adaptability of the Cirendeu village community to modern media during the Covid-19 pandemic based on local wisdom while still based on local culturalsocial values.